2007
DOI: 10.1007/s00248-006-9193-y
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Unexpected Prokaryotic Diversity in Water and Sediments of the Alkaline, Hypersaline Lakes of the Wadi An Natrun, Egypt

Abstract: The phylogenetic diversity of the bacterial and archaeal community in the water and sediments of three large lakes of the Wadi An Natrun was investigated using 16S rRNA clone libraries. The bacterial community was diverse: 769 clones formed 345 operational taxonomic units (OTUs) defined at 99% 16S rRNA sequence identity. The bacterial community in both the water and sediments of the lakes was dominated by clones affiliated with the low G + C Gram-type-positive group, alpha-proteobacteria, and Bacteroidetes, (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
108
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(129 citation statements)
references
References 50 publications
18
108
2
1
Order By: Relevance
“…Sequences related to the species Aquiflexum balticum were also found by cultivation. The detection of phylotypes related to Bacteroidetes as one of the predominant groups is in agreement with the previous cultivation independent studies performed on the bacterial communities inhabiting soda lakes (Humayoun et al 2003;Mesbah et al 2007;Rees et al 2004). …”
supporting
confidence: 92%
See 4 more Smart Citations
“…Sequences related to the species Aquiflexum balticum were also found by cultivation. The detection of phylotypes related to Bacteroidetes as one of the predominant groups is in agreement with the previous cultivation independent studies performed on the bacterial communities inhabiting soda lakes (Humayoun et al 2003;Mesbah et al 2007;Rees et al 2004). …”
supporting
confidence: 92%
“…However, many Böddi-szék clones showed the highest sequence similarities to uncultured environmental clones originating from similar saline and alkaline aquatic environments (Dimitru et al 2008;Humayoun et al 2003;Mesbah et al 2007). In accordance with our results, studying the prokaryotic communities inhabiting the water and sediment of Wadi an Natrun lakes (Egypt), Mesbah et al (2007) also revealed an unexpected phylogenetic diversity and found that none of their rarefaction curves obtained from the analysis of clone libraries reached plateaus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations